Mekenics a social game-based regional language learning toolkit with RFID technology for native Filipino-speakers in Metro Manila aged 18-25 years - Tan, Hans Frederic L.
With more than 170 indigenous languages spoken all over the Philippines, local language barriers are commonplace. Despite the interest in regional languages, regional language learning as well as language acquisition remain low because of the established perceived difficulty involved in learning a language. Public access to convenient regional language learning materials as well as language teachers can also be very limited when compared to those of non-indigenous languages. For this thesis, research was conducted on various topics such as the close relationship of Philippine languages, various language education strategies, Philippine board game culture, as well as some of the new technologies currently applied in education in order to be able to design a product that could help promote and facilitate regional language learning. The final product is Mekenics; it is a Capampangan learning card game with an application of radio-frequency identification (RFID) technology targeted at Metro Manila native Filipino-speakers aged 18-25 years. It is designed to address the challenges learners associate with regional language such as the lack of accessible audible language models, sustaining interest while learning confusing vocabulary and grammar, and the opportunity to practice language organically, all through card game gameplay.